Revitalisasi: Kai Mura Le dalam Tradisi Lisan Dolo: The Revitalization: Kai Mura Le in The Dolo Oral Tradition - Ferdinandus Moses (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2021)
Dolo’s oral tradition is an authentic Lamaholot mass dance that is rich in literacy, as sole, oha, lili, and dolo itself. This research is focused on dolo at Adobara Island, East Flores, East Nusa Tenggara. The research is describing the interpretation on Kai Mura Le, the literature used on literature revitalization stage at Horinara village, Adonara. Qualitative methodology is applied by collecting data from field observation, interview, and literature study. Thus research is expected to be (1) a documentary of oral literature performance, and (2) a rejuvenated passion on oral artistic tradition in community basis by maximizing the literature’s power as the frontline in bringing everyday issues that has potential as a social control system which has humanity, holistic responsibility; and contextually in principle.